Paternalismo industrial y control social. Las experiencias disciplinadoras en la minería del carbón en Chile, Lota y Coronel en la primera mitad del siglo XX - Hernán Venegas Valdebenito (Les Cahiers ALHIM)
The paper focuses on the analysis of extensive control practices in the field of coal mining in Southern Chile. The article examine the transformations of these strategy, particularly those recognized under the concept of patronage and paternalism industrial, and how the latter is characterized by the intensity of control and sense of it all-encompassing. Finally we examine like industry paternalism built a utopian horizon in industrial coal communities Lota and Coronel and influenced indeed in shaping the lives of hundreds of workers and their families.